Ex-ante financial analysis to compare the impact of different control strategies for trypanosomiasis and tick-borne diseases in the coastal lowlands of Kenya - Muraguri, G.R.; McLeod, A.; McDermott, John J. (International Society for Veterinary Epidemiology and Economics, 2000)
De Castro has reviewed the methods applied for the control of ticks and tick-borne diseases (TTBDs). Similarly, Holmes & Ton reviewed the control methods for tsetse flies and trypanosomosis. Although many areas of Kenya, including the Coastal lowlands region, are endemic for TBDs and trypanosomosis, extension messages and control packages are usually targeted at individual diseases. During recent studies, it was observed that smallholder farmers used synthetic pyrethroid pour-on (SPPs) and zero-grazing units enclosed in fly proof nets (referred to as netted units) for the control of TBDs and trypanosomosis. In this paper, the ex-ante financial implications of these two methods are compared to standard acaricide use.